Clinicopathological differences between the motor onset and psychiatric onset of Huntington's disease, focusing on the nucleus accumbens. Issue 5 (2nd July 2019) - Hirano, Mitsuaki; Iritani, Shuji; Fujishiro, Hiroshige; Torii, Youta; Habuchi, Chikako; Sekiguchi, Hirotaka; Yoshida, Mari; Ozaki, Norio
Abstract : Huntington's disease (HD) is an autosomal‐dominant neurodegenerative disorder characterized by the presence of chorea, psychiatric symptoms, and dementia. Although motor symptoms are thought to be correlated with the degeneration of the striatum, there is little information regarding the neuropathological basis of psychiatric symptoms. The ventral part of the striatum is known as the nucleus accumbens (Acb) and is a region of interest as a responsible focus of psychiatric symptoms. The purpose of this study was to investigate the neuronal changes in the Acb and its relevance to psychiatric symptoms in HD. We investigated the brains of 16 HD patients (three patients presented psychiatric symptoms as the onset phenotype (HD‐P), 13 patients presented motor symptoms as the onset phenotype (HD‐M)) and four control subjects. The numerical cell densities for each of the large and small striatal neurons in the Acb, caudate nucleus and putamen were measured at three levels from the caudal to rostral region. As the result, the median small neuronal densities in all striatal regions in the HD brains were significantly lower than controls. Regarding the median small neuronal density in the caudate nucleus and putamen among the three levels, there were significant differences in the HD brains, but not in controls. The median large neuronal density in the Acb was significantly higher in the HD‐P than in the HD‐M, but there was no difference in the median small neuronal density between them. In the present study, we revealed that the Acb as well as the caudate nucleus were affected in HD brains. In terms of neuronal size and caudal to rostral levels, non‐uniform neurodegeneration was observed in the striatum of the HD brains. The pathological difference in the Acb between HD‐P and HD‐M may be one of the factors involved in the development of psychiatric symptoms.